THE IMPACT OF QURANIC LEARNING ON THE DEVELOPMENT OF ISLAMIC CHARACTER AMONG SECOND-SEMESTER STUDENTS AT STIT PALAPA NUSANTARA - M. Ali Karmani (Journal of Islamic Religious Studies, 2024)
This study investigated the impact of Qur'anic learning on the development of Islamic character among second-semester students at STIT Palapa Nusantara. Using a quantitative approach with a correlational survey design, the research examined the relationship between participation in Qur'anic learning and character development. The sample comprised 25 students selected through purposive sampling. Data were collected via a 30-item closed-ended questionnaire, and both descriptive and inferential statistical analyses were conducted. The results showed an average participation score of 4.2 and an average character development score of 4.5. A Pearson correlation test revealed a significant positive correlation (r = 0.67, p = 0.001), indicating that greater participation in Qur'anic learning was associated with enhanced Islamic character development. These findings supported the hypothesis that active engagement in Qur'anic learning positively contributed to character development. The study underscored the importance of integrating Qur'anic values into educational practices, suggesting that effective Qur'anic education can significantly influence students' moral and ethical growth. The results have practical implications for curriculum development and teaching methods in Islamic higher education, emphasizing the role of participatory religious learning in shaping character. Future research should address the study's limitations, such as the small sample size and the need for qualitative insights, to further explore the effects of Qur'anic education on character development.